Determination of respirable-sized crystalline silica in different ambient environments in the United Kingdom with a mobile high flow rate sampler utilising porous foams to achieve the required particle size selection. (June 2018) - Stacey, Peter; Thorpe, Andrew; Roberts, Paul; Butler, Owen
Abstract: Inhalation of respirable crystalline silica (RCS) can cause diseases including silicosis and cancer. Levels of RCS close to an emission source are measured but little is known about the wider ambient exposure from industry emissions or natural sources. The aim of this work is to report the RCS concentrations obtained from a variety of ambient environments using a new mobile respirable (PM4 ) sampler. A mobile battery powered high flow rate (52 L min −1 ) sampler was developed and evaluated for particulate aerosol sampling employing foams to select the respirable particle size fraction. Sampling was conducted in the United Kingdom at site boundaries surrounding seven urban construction and demolition and five sand quarry sites. These are compared with data from twelve urban aerosol samples and from repeat measurements from a base line study at a single rural site. The 50% particle size penetration (d50 ) through the foam was 4.3 μm. Over 85% of predict bias values were with ±10% of the respirable convention, which is based on a log normal curve. Results for RCS from all construction and quarry activities are generally low with a 95 th percentile of 11 μg m −3 . Eighty percent of results were less than the health benchmark value of 3 μg m −3 used in some states in America for ambient concentrations. The power cutting of brick and the largest demolition activities gave the highest construction levels. Measured urban background RCS levels were typically below 0.3 μg m −3 and the median RCS level, at a rural background location, was 0.02 μg m −3 . These reported ambient RCS concentrations may provide useful baseline values to assess the wider impact of fugitive, RCS containing, dust emissions into the wider environment. Highlights: Development of a high flow rate mobile respirable sampler using foam selectors. 85% of bias values from the respirable convention were within ±10%. 95% of quarry and demolition and construction site RCS values were below 11 μg m −3 . Urban RCS vales were 0.3 μg m −3 compared with a median of 0.02 μg m −3 in rural air. A Sahara dust emission event was distinguishable from the rural background.